2013
DOI: 10.5812/hepatmon.7481
|View full text |Cite
|
Sign up to set email alerts
|

Frequency and Genotype of Hepatitis D Virus Infection in Patients Infected with HIV and Those Undergoing Hemodialysis

Abstract: BackgroundHepatitis D virus (HDV) is a defective virus dependent on hepatitis B virus (HBV) for its replication. Due to HDV transmission routes, patients undergoing hemodialysis and those with HIV infection are at risk of acquiring HDV.ObjectivesThis study was aimed to determine the frequency and genotype of HDV infection among patients with HIV infection and those undergoing hemodialysis.Patients and Methods720 cases including 120 patients undergoing hemodialysis, and 600 patients with HIV infection were stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 33 publications
3
12
2
Order By: Relevance
“…Previous HDV and HEV studies have reported the presence of HEV and HDV infections in different regions of the Iran (13, 22); however, there is not enough information regarding HIV co -infection in the Iran. In another study, HIV infected patients has also been reported a low anti -HDV prevalence in the Iran, however, the number of patients is increasing (21). The finding of the present study showed that ALT mean levels among group II and group III patients were higher than that among group I patients.…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…Previous HDV and HEV studies have reported the presence of HEV and HDV infections in different regions of the Iran (13, 22); however, there is not enough information regarding HIV co -infection in the Iran. In another study, HIV infected patients has also been reported a low anti -HDV prevalence in the Iran, however, the number of patients is increasing (21). The finding of the present study showed that ALT mean levels among group II and group III patients were higher than that among group I patients.…”
Section: Discussionsupporting
confidence: 44%
“…Thus, in a study in 2013 by Aghasadeghi et al, it was reported that the HDV infection in patients infected with HIV was among undergoing hemodialysis (21). In another study in Bushehr (South of Iran), Naeimi et al, showed positive serological cases for HEV among blood donors (22).…”
Section: Introductionmentioning
confidence: 95%
“…Nested PCR gained popularity in the early 1990s after Nichol and colleagues used nested PCR reactions to identify a novel hantavirus during an outbreak of a highly pathogenic acute respiratory illness (Nichol et al, 1993). Nested PCR reactions have been employed to detect a number of viruses (Aghasadeghi et al, 2013; Lam et al, 2007; Song et al, 2009), but not yet for RVA until this study.…”
Section: Discussionmentioning
confidence: 99%
“…In another study on 606 HBsAg-positive patients in Mashhad, HDVAb was found in the serum of 35 patients, representing a prevalence of around 5.8% (7). Another study on patients, who were receiving hemodialysis in Tehran found that 7.5% of the cases were HBsAg-positive and 33.3% of HBsAg-positive patients were HDVAb-positive (8). However, a study on 153 hemodialysis patients in the south of Iran showed that nine (5.88%) were HBsAg-positive and none suffered from hepatitis D (9).…”
Section: Introductionmentioning
confidence: 97%
“…The current findings also showed that the prevalence of HBsAg positivity among 108 hemodialysis patients was 3.7%. Previous studies in Iran reported that 5.88% to 7.5% of hemodialysis patients were HBsAg-positive (8,9,19,20). This rate among 76 hemodialysis and BTM patients in Iran was 7.89% (21).…”
Section: P R O O Fmentioning
confidence: 99%